Breath biomarkers in diagnostic applications - Pham, Y Lan; Beauchamp, Jonathan (Molecules, 2021)
The detection of chemical compounds in exhaled human breath presents an opportunity to determine physiological state, diagnose disease or assess environmental exposure. Recent ad-vancements in metabolomics research have led to improved capabilities to explore human metabolic profiles in breath. Despite some notable challenges in sampling and analysis, exhaled breath repre-sents a desirable medium for metabolomics applications, foremost due to its non-invasive, convenient and practically limitless availability. Several breath-based tests that target either endogenous or exogenous gas-phase compounds are currently established and are in practical and/or clinical use. This review outlines the concept of breath analysis in the context of these unique tests and their applications. The respective breath biomarkers targeted in each test are discussed in relation to their physiological production in the human body and the development and implementation of the associated tests. The paper concludes with a brief insight into prospective tests and an outlook of the future direction of breath research.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Breath tests; Clinical practice; Exhaled biomarkers; Exhaled breath; Metabolomics; Volatile organic compounds